PERBEDAAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS DAN MOTIVASI BELAJAR DENGAN PEMBELAJARAN BERBASIS MASALAH - Irham Habibi Harahap (Program Studi Pendidikan Guru Sekolah Dasar Universitas Nahdlatul Ulama Sumatera Utara, 2017)
The aim of this research is to find out (1) the differences of mathematics problem solving ability of student who get the problem-based learning better than student who get direct learning, (2) the difference of students’ learning motivation who get problem-based learning better than student who get direct learning, (3) the level of students’ activity during the process of the problem-based learning takes place, (4) the process of students’ answers that taught with problem-based learning is better than direct learning. Thisresearch is a semi experimental research. The population of this study is the students of eighth grade of Junior High School that accredited A in Sibuhuan. Randomly, one school was chosen as a subject of this research, namely SMP Negeri 1 Barumun. Then randomly, selected two classes from seven classes The first experiment class was given a problem-based learning treatment and the second experiment class was given a direct learning treatment. Instrument which is used consisted of a test of mathematics problem solving ability, questionnaire of students’ learning motivation and observation sheets. Data analysis was done by covariance analysis (ANACOVA) and Mann-Whitney test. The result of this research is the whole students who get problem-based learning is significantly better than the mathematics problem solving ability and students’ learning motivation are compared with students who get direct learning, students’ activity in problem-based learning is effective and the process of students’ answer which get problem-based learning better than students who get direct learning.